If (x+iy)^2=8i,prove that x((x^2)-3(y^2)=y((y^2)-3(x^2)=2,show that these equations have one solution in which x=y.And hence find one of the cube root of 2-2i.Find the quadratic equation satisfied by the other cube roots of 2-2i
If (x+iy)^2=8i,prove that x((x^2)-3(y^2)=y((y^2)-3(x^2)=2,show that these equations have one solution in which x=y.And hence find one of the cube root of 2-2i.Find the quadratic equation satisfied by the other cube roots of 2-2i
Sorry, u r right ,the question was wrong.
Any idea will be appreciated ,pls do solve the prb without using de moviers theorem
If (x+iy)^3=8i,where x and y are real nos prove that x((x^2)-3(y^2)=y((y^2)-3(x^2)=2,show that these equations have one solution in which x=y.And hence find one of the cube root of 2-2i.Find the quadratic equation satisfied by the other cube roots of 2-2i
ans -i-i;z^2-(i+i)z+2i=0;0.5(1+sqrt 3)+0.5(1-sqrt 3)i,0.5(1-sqrt 3)+0.5(1+sqrt 3)i
I believe Plato was referring to the parenthesis, not to mention the fact that neither $\displaystyle x(x^2) - (3y^2)$ nor $\displaystyle x(x^2 - 3y^2)$ are equal to 2. Check the problem statement again.
And de Moivre's theorem doesn't play into this. Just expand $\displaystyle (x + iy)^2$ and match coefficients with 8i. (Which is what Plato did.)
-Dan